563 Pharmacodynamics and pharmacokinetics of SO-C101 in cynomolgus monkeys. (9th November 2020) - Podzimkova, Nada; Adkins, Irena; Martynoff, Guy de; Bechard, David; Spisek, Radek; Moebius, Ulrich
Abstract : Background: SO-C101 is a superagonist fusion protein of interleukin (IL)-15 and the IL-15 receptor α (IL-15Rα) sushi+ domain. SO-C101 effectively stimulates natural killer (NK) cells and memory CD8+ T cells with no significant expansion and activation of regulatory T cells which translates to anti-tumor efficacy in mouse. Methods: In this study, we investigated different administration schedules of SO-C101 in cynomolgus monkeys to assess its pharmacodynamics and pharmacokinetics properties using intravenous (IV) and subcutaneous (SC) routes of administration. Results: Subcutaneous administration of SO-C101 was more effective than IV administration in terms of activating thee target immune cells which was correlated to the differences in SO-C101 exposure. Repeated administration of SO-C101 over two weeks promoted an increase of absolute lymphocyte counts and of the circulating NK and CD8+ T cell numbers. Moreover, two administrations on consecutive days were optimal and comparable to four daily administrations. We further determined an optimal schedule for a repetitive SO-C101 SC administration to achieve a cycle-dependent stimulation of NK and CD8+ T cells over the course of 10 weeks. These studies allowed to correlate the concentration to response relationship in vitro with the relationship between Cmax following SC administration and the resulting NK and CD8+ T cell activation levels in vivo. These data were used to determine the starting dose and subsequent dose escalation steps of SO-C101 in an ongoing Phase I clinical trial in patients with advanced solid tumors. Conclusions: Since the potency of SO-C101 to activate NK and CD8+ T cells in vitro is equivalent between human and cynomolgus monkeys, these studies informed the dose and schedule selection for the ongoing Phase I clinical study (NCT04234113 ). Ethics Approval: Pharmacodynamics and pharmacokinetics studies in cynomolgous monkeys were approved by Ethics Board of an appropriate contract research organizations (CROs)